A Cultural Content: An Analysis Of English Textbooks, Pathway To English, And Talk Active English - Sri Suci Surayawati; Shinta Renika (Sean Institute, 2024)
This study examined the cultural content in reading texts from three English textbooks by different publishers. The objective was to identify the cultures represented, determine the most dominant cultures, and analyze how these cultures are portrayed in the textbooks. A descriptive qualitative research approach was used, with documentation serving as the primary instrument for data collection. Data was gathered through document analysis and processed using three key steps: data condensation, data display, and drawing and verifying conclusions. The study yielded several key findings. First, it was observed that the three textbooks included elements of source culture, target culture, and international culture. Second, source culture was the most frequently represented, surpassing both target and international cultures. Third, the most prominent cultural aspect was aesthetic sense, which appeared more frequently than sociological, semantic, or pragmatic senses, with percentages of 52.63% in Bahasa Inggris, 50% in Pathway to English, and 51.43% in Talk Active. Based on these findings, the researcher recommends that English teachers develop a strong understanding of the cultural content within these textbooks to better explain cultural materials that may vary across textbooks.